Defective membrane function in a patient with severe combined immunodeficiency disease. - Gehrz, R C (1980)
We report a girl with severe combined immunodeficiency with functional impairment of both humoral and cellular immunity despite normal numbers of B and T lymphocytes. Immunologic studies revealed hypergammaglobulinaemia, absent migratory response by polymorphonuclear leucocytes to chemoattractants, and diminished lymphocyte proliferative responses to mitogens, antigens and allogeneic leucocytes. However, stimulation of the patient's mononuclear leucocytes with the calcium ionophore, A23187, resulted in a normal proliferative response. We therefore postulate a membrane defect as the basis for immunologic dysfunction in this child.